The Quality of Essay Writing of Indonesian EFL Learners - Qonitatun Qonitatun (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2016)
There is an assumption that the writing ability of the forth semester students have been improved because the students have learned about how to develop paragraph in writing I, writing II, and writing III subject, so they are expected able to develop an essay. The purposes of the study are to describe the organization of the essay developed by the students of Widyagama University and to know the grammar problems found in the sentences of the essay developed by the students of Widyagama University. Based on finding and discussion of the research, the researcher concludes that the organization of the essays that developed by the research subjects is poor. Only one essay has a complete organization. The developing paragraph of each essay is also poor. Most of the paragraphs don’t have concluding sentence. Generally, the essays had covered four types of the sentences; simple sentence, compound sentence, complex sentence, and compound-complex sentence. However, the essays are dominated by only one type of sentences, simple sentence. The grammar problems that found are fragment sentence, the errors of subject-verb agreement, and the errors in using coordinating conjunction